2018
DOI: 10.1177/1087724x18808533
|View full text |Cite
|
Sign up to set email alerts
|

New Starts, Growing Inequities: Federal and Local Public Transit Funding

Abstract: Equity concerns regarding local revenue sources are increasingly important in the United States, as local sales taxes for transportation increase amid perceived federal funding shortfalls. This study examines shifts in the federal role and local funding sources for public transit projects supported by the New Starts program. The analysis finds that total federal New Starts spending grew over this period, but was distributed across more costly projects, with a resulting decrease in the average federal share per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…How we pay for transportation, the sources of funds, and rules about their distribution are important aspects of equity (Lowe & Hall, 2019). In a study by Lee et al (2017), it was found that the distribution of transportation infrastructure funds for the improvement of communities often favors more advantaged groups (middle-class suburban neighborhoods).…”
Section: Literature Reviewmentioning
confidence: 99%
“…How we pay for transportation, the sources of funds, and rules about their distribution are important aspects of equity (Lowe & Hall, 2019). In a study by Lee et al (2017), it was found that the distribution of transportation infrastructure funds for the improvement of communities often favors more advantaged groups (middle-class suburban neighborhoods).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intra-regional competition for these funds often means that low-income communities with lower civic or advocacy capacity are less likely to receive funding (Lowe et al, 2016). The mechanisms of federal funding and regional transportation planning through Metropolitan Planning Organizations (MPO) have clearly stated equity requirements, but funding decisions at the state and local level can bypass projects with an equity focus or introduce regressive funding mechanisms that lessen the positive impacts (Lowe, 2014;Lowe & Hall, 2019). Avoiding these mistakes and understanding how best to use available funds for those most in need is essential in moving forward.…”
Section: Literature Reviewmentioning
confidence: 99%